Evaluation of the Antidiarrhoeal Activity of Aqueous Stem Bark Extract of Terminalia catappa in Castor oil-induced Diarrhoeal Albino Rats (Fountain Journal of Natural and Applied Sciences, 2022)
Diarrhoeal illness remains a key global health problem causing 15% of deaths among children under five years of age. This study evaluated the antidiarrhoeal activity of Terminalia catappa aqueous stem bark extract on albino rats. Antidiarrhoeal activity of T. catappa was assessed by measuring the stool inhibition, gastrointestinal motility and castor oil-induced enteropooling. Thirty (30) albino rats were divided into 6 groups of 5 rats each, where groups I and II remained the normal and negative control groups respectively; group III was treated with standard drug, groups IV, V and VI were treated with 100, 200 and 300 mg/kg b. wt. of aqueous stem bark extract of T. catappa, respectively. Percentage stool inhibition of treated groups was significantly greater than that of the negative control. However, group II treated with standard drug (loperamide) showed higher percentage inhibition. The volume of intestinal fluid decreased with increase in dose of the extract. The volume of intestinal fluid of the group treated with standard drug significantly decreased when compared to group treated with extract. Distance travelled by the charcoal significantly decreased at higher dose of extract. Aqueous stem bark extract of T. catappa has a dose-dependent antidiarrhoeal activity. Keywords: Stool inhibition, diarrhoea, enteropooling, gastrointestinal motility, Terminalia catappa
Keywords: stool inhibition; diarrhea; enteropooling; gastrointestinal motility; Terminalia catappa